2023
DOI: 10.3390/jcm12020441
|View full text |Cite
|
Sign up to set email alerts
|

A Novel Predictive Model of Pathological Lymph Node Metastasis Constructed with Preoperative Independent Predictors in Patients with Renal Cell Carcinoma

Abstract: Introduction: Renal cell carcinoma (RCC) is one of the most common urinary tumors. The risk of metastasis for patients with RCC is about 1/3, among which 30–40% have lymph node metastasis, and the existence of lymph node metastasis will greatly reduce the survival rate of patients. However, the necessity of lymph node dissection is still controversial at present. Therefore, a new predictive model is urgently needed to judge the risk of lymph node metastasis and guide clinical decision making before operation. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 23 publications
0
4
0
Order By: Relevance
“…This model shows potential for the more precise presurgical prediction of LNM-RCC, thereby enabling earlier clinical interventions and potentially improving patient prognosis. [73] Lymph node dissection (LND) has been proposed as a strategy to improve the outcomes of surgical therapy for many genitourinary malignancies. Nonetheless, the therapeutic efficacy of LND in RCC remains a subject of debate.…”
Section: Ln Metastasis From Rcc (Lnm-rcc)mentioning
confidence: 99%
See 1 more Smart Citation
“…This model shows potential for the more precise presurgical prediction of LNM-RCC, thereby enabling earlier clinical interventions and potentially improving patient prognosis. [73] Lymph node dissection (LND) has been proposed as a strategy to improve the outcomes of surgical therapy for many genitourinary malignancies. Nonetheless, the therapeutic efficacy of LND in RCC remains a subject of debate.…”
Section: Ln Metastasis From Rcc (Lnm-rcc)mentioning
confidence: 99%
“…This model shows potential for the more precise presurgical prediction of LNM-RCC, thereby enabling earlier clinical interventions and potentially improving patient prognosis. [73]…”
Section: The Site Of Rcc Metastasismentioning
confidence: 99%
“…Therefore, a novel predictive model of pathological LN metastasis constructed with preoperative independent predictors in patients with RCC is urgently needed. Luckily, a recent study by Sun JX et al concluded that Low age, large LN size in preoperative imaging, and high clinical T stage could be used as independent predictive factors of pathological LN metastasis in patients with RCC [38].…”
Section: Limitationsmentioning
confidence: 99%
“…Babaian et al (8) noted that LN dissection (LND) can improve the 5-year survival rate of patients with LN involvement, suggesting that patients with renal cancer undergoing LND may have better survival. LN infiltration is one of the most important predictors of tumor progression and mortality (9). Therefore, it is imperative to investigate the strong predictors of LN metastasis and accurately identify at-risk patients who require LND.…”
Section: Introductionmentioning
confidence: 99%